A review of numerical modelling of high-temperature phase change material composites for solar thermal energy storage. (June 2020) - Liu, Ming; Sun, Yanping; Bruno, Frank
Highlights: Numerical models to describe heat transfer process in PCM composites were reviewed. Natural convection in liquid PCM is considered in metal and ceramic composites. A simplified heat conduction model is usually applied in graphite composites. Graphite leads to higher heat transfer enhancement than metal with similar porosity. Abstract: High-temperature phase change materials (PCMs), due to their high energy density and capability of maintaining nearly constant temperature, have been widely investigated to replace the current molten salt sensible storage system in concentrated solar thermal power plants. However, the performance of the PCM storage system is severely restricted by the low thermal conductivity and high corrosion of molten salt PCMs. Fabrication of PCM into PCM composite is a promising and effective method to improve the usability and handleability of high-temperature PCMs. The feasibility of fabrication process and material characterisation has been conducted through laboratory-scale experiments. This work reviews mathematical models used to describe the heat transfer process in high-temperature PCM composites, and hence to simulate the thermal performance of the storage system. It is critical to design a high efficiency storage system via numerical modelling. In order to include the natural convection in liquid PCM, the fundamental governing equations of continuity, momentum and energy need to be applied in the numerical model, together with the heat conduction equation in the solid structure material and the heat convection equation between the PCM and structure material. This detailed model is usually applied in metal and ceramic composites where the pore size is large, and the equations are usually solved by using commercial computational fluid dynamics software. For graphite-based composites, the model can be simplified into the energy equation with thermal equilibrium between the PCM and graphite.